Story telling in space and time - Ray, David (The University of Edinburgh, 2014)
An Android based smartphone application called PuzzleMappingAdventure is an exploratory tourist oriented story telling application which was built using GIS techniques. The story which is created is open for interpretation and defined through user choices using linear and non-linear, dynamic and interactive storylines which take a user on an adventure through the Old Town of Edinburgh City. Using proximity alerts a user will activate locational specific information at points of interest defined within three set routes through the city. User evaluation data were acquired from a questionnaire using a six level Likert scale and processed using importance-performance analysis. Results revealed overall satisfactory to high level of satisfaction with the application where importance and performance aligned favourably. The application effectively enables tourist exploration without infringing temporal or spatial limitations on to the user, whilst meeting information demand requirements. User interface and controls may be deemed as limiting factors within the design of the application together with GPS inaccuracies.
Keywords: Android; MSc Geographical Information Science; GIS